Pengaruh Art Therapy dan Self-Esteem Terhadap Hasil Belajar Siswa - Lilis Lela Sandy; Yuyun Wahyuni; AM Masruri (Peneliti.net, 2022)
The purpose of this study was to determine the effect of art therapy and self-esteem on learning outcomes. This research method is quantitative, the instrument used is a questionnaire. Population and sample of class XI students of MAN 1 Serang Regency in the academic year 2021/2022 Odd, the population is 252 students of class XI, the research sample is 100 students chosen randomly. Data collection is done by distributing questionnaires. Data analysis with descriptive statistical methods, and multiple regression analysis. The results showed that there was an effect of art therapy (X1) and self-esteem (X2) on learning outcomes (Y), this is evidenced by the regression calculation which shows the value of F arithmetic > F table or 26.557 > 3.11 and Sig. 0.000 <0 ,05. While the coefficient of determination of 85.4% indicates that the contribution of Art Therapy (X1) and Self-esteem (X2) together to student learning outcomes (Y) is 85.4%, the rest (14.6%) is due to the influence of other factors. It can be said that art therapy and self-esteem have a significant effect on student learning outcomes.